Differences in peripheral oxidative stress markers in Alzheimer's disease, vascular dementia and mixed dementia patients. (December 2015) - Hatanaka, Hirokuni; Hanyu, Haruo; Fukasawa, Raita; Hirao, Kentaro; Shimizu, Soichiro; Kanetaka, Hidekazu; Iwamoto, Toshihiko
Abstract : Aims: We determined whether the possible roles of oxidative stress differ in the pathophysiology and cognitive decline of Alzheimer's disease (AD), vascular dementia (VaD) and mixed Alzheimer's/vascular dementia (MD). Methods: We measured the levels of diacron reactive oxygen metabolite (dROM), reflecting the amount of organic hydroperoxides, and biological anti‐oxidant potential (BAP), measuring the ferric reducing ability of blood plasma, in 72 patients with AD, 27 with VaD, 24 with MD and 53 non‐demented outpatients (control group). In addition, endogenous plasma anti‐oxidants, such as albumin, total bilirubin and uric acid, were compared among the groups. All participants with VaD and MD showed extensive white matter hyperintensity, in addition to multiple lacunes. Results: The dROM levels were significantly higher in the AD and MD groups than in the control group. The BAP levels were significantly lower in the MD group than in the control, AD and VaD groups. The AD group showed significantly lower levels of bilirubin and uric acid than the control group. The MD group showed a significantly lower level of albumin than the control and AD groups, and a significantly lower level of bilirubin than the control group. The Mini‐Mental State examination scores correlated significantly with dROM levels and BAP/dROM ratios in the AD group. Conclusions: An imbalance in pro‐oxidant and anti‐oxidant defenses is apparently involved in the pathophysiology of the AD and MD groups. The extent of oxidative stress damage might differ in subtypes of dementia by being greater in the MD group than in other types of dementia. Synergic effects of the degenerative element of AD and white matter lesions might be associated with oxidative stress damage in the MD group. Geriatr Gerontol Int 2015; (Suppl. 1): 53–58.